2009
DOI: 10.1161/strokeaha.108.527606
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Stroke Unit on Length of Hospital Stay and In-Hospital Case Fatality

Abstract: Background and Purpose-Randomized trials have demonstrated reduced morbidity and mortality with stroke unit care; however, the effect on length of stay, and hence the economic benefit, is less well-defined. In 2001, a multidisciplinary stroke unit was opened at our institution. We observed whether a stroke unit reduces length of stay and in-hospital case fatality when compared to admission to a general neurology/medical ward. Methods-A retrospective study of 2 cohorts in the Foothills Medical Center in Calgary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 28 publications
0
59
2
3
Order By: Relevance
“…13 Zhu et al 14 found that the adjusted odds of an LOS more than 7 days were reduced by 30% on a stroke unit compared with general neurology/medical wards. Similarly, the presence of in-house core trauma surgeons and physician assistants improved management and outcome (including reduced LOS) of critically injured trauma patients within a level I TC.…”
Section: Comparison Between Sci and Non-sci Trauma Centers A Ploumis mentioning
confidence: 99%
“…13 Zhu et al 14 found that the adjusted odds of an LOS more than 7 days were reduced by 30% on a stroke unit compared with general neurology/medical wards. Similarly, the presence of in-house core trauma surgeons and physician assistants improved management and outcome (including reduced LOS) of critically injured trauma patients within a level I TC.…”
Section: Comparison Between Sci and Non-sci Trauma Centers A Ploumis mentioning
confidence: 99%
“…Research that will facilitate implementation is very welcome and should have a high priority. The article published in this issue of Stroke by Zhu et al 11 is an important contribution in this regard. The authors have explored the effects of implementation of SU care in the Calgary Health Region in Canada.…”
Section: How Do We Improve the Implementation Of Stroke Units?mentioning
confidence: 98%
“…Randomized controlled trials have shown conclusively that patients treated in dedicated stroke units fare better than those treated in general wards without the same ready access to personnel trained and experienced in managing stroke. [56][57][58][59] The spectrum of stroke syndrome in these studies included both ischemic and hemorrhagic stroke, ranging from mild (transient ischemic attack and minor stroke) to more severe. 58 In one trial, providing treatment in a stroke unit significantly reduced in-hospital mortality (odds ratio Patients with stroke who receive organized inpatient care in a stroke unit are more likely to be alive, independent and living at home one year after the stroke.…”
mentioning
confidence: 99%
“…[56][57][58][59] The spectrum of stroke syndrome in these studies included both ischemic and hemorrhagic stroke, ranging from mild (transient ischemic attack and minor stroke) to more severe. 58 In one trial, providing treatment in a stroke unit significantly reduced in-hospital mortality (odds ratio Patients with stroke who receive organized inpatient care in a stroke unit are more likely to be alive, independent and living at home one year after the stroke. 57,60,61 These benefits were most apparent in units based in a discrete ward, and there is substantial evidence of avoidance of direct costs when such care is implemented.…”
mentioning
confidence: 99%